1998
DOI: 10.1103/physrevlett.80.3586
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Electron Models with Exact SO(5) Symmetry

Abstract: We construct a class of microscopic electron models with exact SO(5) symmetry between antiferromagnetic and d-wave superconducting ground states. There is an exact one-to-one correspondence between both single-particle and collective excitations in both phases. SO(5) symmetry breaking terms can be introduced and classified according to irreducible representations of the exact SO(5) algebra. The resulting phase diagram and collective modes are identical to that of the SO(5) nonlinear sigma model.Comment: 5 page… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 10 publications
4
90
0
Order By: Relevance
“…Interestingly this field is easily tunable experimentally [34][35][36][37] in the bilayer graphene case. SO(5) symmetry in HTS is conjectured to emerge in low-energy effective theory 21 , and can be exactly realized in extended Hubbard model with artificial longrange interactions 38,39 ; however, it never becomes exact for commonly used models like t − J or Hubbard model. In contrast, SO(5) symmetry and its explicit symmetry breaking naturally appear in the microscopic Hamiltonian (Eq.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Interestingly this field is easily tunable experimentally [34][35][36][37] in the bilayer graphene case. SO(5) symmetry in HTS is conjectured to emerge in low-energy effective theory 21 , and can be exactly realized in extended Hubbard model with artificial longrange interactions 38,39 ; however, it never becomes exact for commonly used models like t − J or Hubbard model. In contrast, SO(5) symmetry and its explicit symmetry breaking naturally appear in the microscopic Hamiltonian (Eq.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Since my review in the Proceedings of the International Conference on Materials and Mechanisms of Superconductivity [3], some important progress has been made due to the efforts of many groups [4][5][6][7][8][9][10][11][12]. There has also been the criticisms raised.…”
mentioning
confidence: 99%
“…2,3,4,5,6,7 Calculations based on NLQσM showed that the features of the phase diagram deduced from the SO(5) theory agree qualitatively with the global topology of the observed phase diagrams of high-T c superconductors. 8 Magnetic correlation functions within the SO(5) theory were investigated showing that the theory predicts a scenario for the evolution of magnetic behaviour, which is qualitatively consistent with experiments.…”
Section: Introductionmentioning
confidence: 62%